Measurement and Analysis of Bubble Size Distribution in the Electrochemical Stirred Tank Reactor - Mahmood , Raghad S.; Alsarayreh, Alanood A.; Abbas, Ammar S. (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
The dimensions of bubbles were measured in a stirrer tank electrochemical reactor, where the analysis of the bubble size distribution has a substantial impact on the flow dynamics. The high-speed camera and image processing methods were used to obtain a reliable photo. The influence of varied air flow rates (0.3; 0.5; 1 l/min) on BSD was thoroughly investigated. Two types of distributors (cubic and circular) were examined, and the impact of various airflow rates on BSD was investigated in detail. The results showed that the bubbles for the two distributors were between 0.5 and 4.5 mm. For both distributors at each airflow, the Sauter mean diameter for the bubbles was calculated. According to the results, as the flow rate raised, the bubble size for cubic distributors increased from 2.35 to 2.41 mm and for circular distributors from 2.76 to 2.88 mm.